Homeostatic regulation of extracellular signal-regulated kinase 1/2 activity and axonal Kv7.3 expression by prolonged blockade of hippocampal neuronal activity - Baculis, Brian C.; Kesavan, Harish; Weiss, Amanda C.; Kim, Edward H.; Tracy, Gregory C.; Ouyang, Wenhao; Tsai, Nien-Pei; Chung, Hee Jung (Frontiers in Cellular Neuroscience, 2022)
Homeostatic plasticity encompasses the mechanisms by which neurons stabilize their synaptic strength and excitability in response to prolonged and destabilizing changes in their network activity. Prolonged activity blockade leads to homeostatic scaling of action potential firing rate in hippocampal neurons in part by decreased activity of N-Methyl-D-Aspartate receptors and subsequent transcriptional down-regulation of potassium channel genes including KCNQ3 which encodes Kv7.3. Neuronal Kv7 channels are mostly heterotetramers of Kv7.2 and Kv7.3 subunits and are highly enriched at the axon initial segment (AIS) where their current potently inhibits repetitive and burst firing of action potentials. However, whether a decrease in Kv7.3 expression occurs at the AIS during homeostatic scaling of intrinsic excitability and what signaling pathway reduces KCNQ3 transcript upon prolonged activity blockade remain unknown. Here, we report that prolonged activity blockade in cultured hippocampal neurons reduces the activity of extracellular signal-regulated kinase 1/2 (ERK1/2) followed by a decrease in the activation of brain-derived neurotrophic factor (BDNF) receptor, Tropomyosin receptor kinase B (TrkB). Furthermore, both prolonged activity blockade and prolonged pharmacological inhibition of ERK1/2 decrease KCNQ3 and BDNF transcripts as well as the density of Kv7.3 and ankyrin-G at the AIS. Collectively, our findings suggest that a reduction in ERK1/2 activity and subsequent transcriptional down-regulation may serve as a potential signaling pathway that links prolonged activity blockade to homeostatic control of BDNF-TrkB signaling and Kv7.3 density at the AIS during homeostatic scaling of AP firing rate.